Applying the developmental model of marital competence to sexual satisfaction: Associations between conflict resolution quality, forgiveness, attachment, and sexual satisfaction. (April 2021) - Allsop, David B.; Leavitt, Chelom E.; Saxey, Matthew T.; Timmons, Joshua E.; Carroll, Jason S.
Sexual satisfaction is a complex construct that is affected by many diverse factors. Without a comprehensive framework guiding their work, scholars and practitioners who work with married couples may inadvertently focus on a single factor affecting sexual satisfaction and subsequently limit the effectiveness of their research and practice. Through discussion and an empirical example, the current study explores how the developmental model of marital competence—a comprehensive theory for understanding marital processes—can be used by scholars and practitioners to guide their work on sexual satisfaction and broaden their approach. Utilizing U.S. nationally representative data from 2, 114 mixed-sex couples and guided by the actor-partner-interdependence-model, cross-sectional and longitudinal associations between wives' and husbands' sexual satisfaction and three factors—conflict resolution quality, forgiveness, and anxious and avoidant attachment—that correspond to the three domains of the developmental model of marital competence—marital communication, marital virtues, and marital identities—were tested. Results of the current study provide empirical support for the use of the developmental model of marital competence when approaching work on sexual relationships among married, heterosexual couples. For both partners, variables from each of the three domains of this model were associated with sexual satisfaction cross-sectionally, and variables in one domain—attachment avoidance and anxiety—were associated with changes in sexual satisfaction over time. The merits of researchers and practitioners integrating the developmental model of marital competence into their work are discussed.